If I do this in sage

```
F=sum(k^2*factorial(n), v=k, a=1, b=n+1); F
```

it correctly expands to what I want:

```
⎛ 3 2 ⎞
⎝2⋅n + 9⋅n + 13⋅n + 6⎠⋅n!
───────────────────────────
6
```

However, if the factorial is a function of the summed variable, it doesn't work anymore:

```
sage: F=sum(k^2*factorial(k), v=k, a=1, b=n+1); F
sum(k^2*factorial(k), k, 1, n + 1)
sage: F.expand_sum()
sum(k^2*factorial(k), k, 1, n + 1)
```

Is this the expected behavior? How can I get it to expand no matter what's inside the summation?

I'm using Sagemath 7.5, by the way.

Thank you.